Retrospective Evaluation of Adult Hydatid Cyst Cases - Sevil Alkan; Mahmut Sünnetçioğu; Tayyar Tarcan; Yusuf Arslan; Deniz Altındağ; Ali İrfan Baran; Mehmet Çelik (Genel Tıp Dergisi)
Aim: The aim of this study was to evaluate the characteristics of adult patients followed up for hydatid cysts disease. Method: Patients over the age of 18 years who were diagnosed with hydatid disease, between January 2015 and September 2021 were included in the study. The clinical, laboratory and radiologic characteristics of the patients were evaluated retrospectively. Results: The study included 66 patients. 59.1% of the patients were female and the mean age was 40.9±15.60 years. The most common presenting symptom was abdominal pain (42.4%). The most common sites of involvement were the liver (78.8%) and lung (18.2%). The majority of patients had solitary cysts (84.8%). The most common finding in laboratory tests was elevated total IgE (74.1%). The indirect hemagglutination (IHA) test was positive in 77.4% of the patients tested. Conclusion: In our study, it was concluded that hydatid cysts are most commonly seen in the liver, often with single organ involvement, and that elevated total IgE in laboratory diagnosis may be helpful in the diagnosis of hydatid cyst disease, although it does not make a definitive diagnosis.